"Can do!" Teacher Promotion of Optimism in Response to Student Failure Expectation Expressions in Classroom Discourse. Issue 3 (15th April 2020) - Vehkakoski, Tanja M.
ABSTRACT: This study offers detailed observational analyses of how teachers use optimism as an instructional resource when responding to students' failure expectation displays in classroom situations. The results were based on video-recordings of 25 lessons in two Finnish part-time special education settings, analysed by means of applied conversation analysis. The results showed that the teachers boosted optimism by inverting students' negative utterances, giving examples of successful experiences of peers, offering praise for students' earlier performance or focusing on problems through instructional support. The study underlines the importance of addressing and elaborating students' negative learning-related self-assessments in classroom interactions.